2021
DOI: 10.21547/jss.836625
|View full text |Cite
|
Sign up to set email alerts
|

Enriching the Meaning With Associations in Advertisements: Semiotic Analysis of Turkcell Fiber Advertising

Abstract: Markaların stratejik iletişim yönetimlerinde reklamlar önemli bir yer tutmaktadır. Günümüz reklamcılık anlayışında markalar hayali dünyalar ile tüketicilerin yaşamlarını ilişkilendirmekte; rakiplerden farklılaşma amacına yönelik olarak tüketicilerde ürüne ait güçlü anlamlar yaratmayı amaçlamaktadır. Reklamda görsel ve dilsel unsurlarda kullanılan mitler, çeşitli semboller ve metaforlar yardımıyla çağrışımlar oluşturularak yeni anlamlar üretme, anlamı transfer etme ve zenginleştirme gibi işlevler yerine getiril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Both create the denotative sign, it is also considered as the connotative signifier (4) thenext stage of the semiotic system. The connotative signifier should create a connotative signified (5) to make a connotative sign as a second phase of signification (6) (Barthes, 1967).…”
Section: Denotation and Connotationmentioning
confidence: 99%
See 1 more Smart Citation
“…Both create the denotative sign, it is also considered as the connotative signifier (4) thenext stage of the semiotic system. The connotative signifier should create a connotative signified (5) to make a connotative sign as a second phase of signification (6) (Barthes, 1967).…”
Section: Denotation and Connotationmentioning
confidence: 99%
“…The study was descriptive qualitative research. The results revealed that the firstorder and second-order signification proposed by Barthes (1967) could be used in analysing the four sign systems. connotations represented the communication that occurred between the signs and the viewers' emotions.…”
mentioning
confidence: 98%